Refraction difference value variations in children and adolescents with different refractive errors - Da-Wen Wu; Ze-Yi Yang; Yan Nie; He-Ya Ye; Liang Chen; Long-Qian Liu; Guo-Yuan Yang (International Journal of Ophthalmology)
AIM: To evaluate the refraction difference value (RDV) variations in children and adolescents with different refractive errors and analyze its correlation with refractive development. METHODS: Participants aged 4-16y with different refractive statuses (hyperopia, emmetropia, myopia) underwent comprehensive eye examinations, including spherical equivalent (SE) refraction, axial length (AL), total RDV (TRDV), and RDVs at various eccentricities (0°-15°, 15°-30°, 30°-45°) and quadrants (inferior, superior, nasal, temporal). Statistical analysis involved one-way ANOVA for group comparisons and Pearson correlation for examining relationships between SE/AL and RDVs. Paired t-tests compared quadrant-specific RDVs within groups. RESULTS: Significant difference was found in TRDV (P<0.001), RDV15°-30° (P=0.033), RDV30°-45° (P<0.001), RDV-inferior (RDV-I, P<0.001) and RDV-temporal (RDV-T, P<0.001) among hyperopia, emmetropia and myopia group. Pearson correlation analysis revealed a negative correlation of SE with TRDV (P=0.001), RDV30°-45° (P=0.004), RDV-I (P=0.047), and RDV-T (P<0.001). The differences between RDV-superior (RDV-S) and RDV-I were statistically significant in all groups (P<0.001 for all) and between RDV-T and RDV-nasal (RDV-N) were statistically significant in hyperopia group (P<0.001). Within the pre-myopic group, the analysis revealed a negative correlation of SE with RDV-I (P=0.009). Pearson correlation analysis revealed a positive correlation of AL with TRDV (P=0.036), RDV15°-30° (P=0.004), RDV30°-45° (P<0.001), RDV-S (P=0.003), RDV-I (P<0.001), RDV-T (P<0.001), RDV-N (P=0.022), while revealed a negative correlation of AL with RDV0-15° (P=0.018). CONCLUSION: Our study indicates TRDV, RDV30°-45°, RDV-I, RDV-T may relate to refractive development, and a negative correlation between SE and RDV-I in pre-myopic children.